Impact of Sumadhur intervention on fertility and family planning decision-making norms: a mixed methods study - Ashley Mitchell; Mahesh C. Puri; Minakshi Dahal; Alia Cornell; Ushma D. Upadhyay; Nadia G. Diamond-Smith (BMC, 2023)
Abstract Background Mindful of social norms shaping health among women pressured to prove early fertility in Nepal, a bi-national research team developed and piloted a 4-month intervention engaging household triads (newly married women, their husbands, and mothers-in-law) toward advancing gender equity, personal agency, and reproductive health. This study evaluates the impact on family planning and fertility decision-making. Methods In 2021, Sumadhur was piloted in six villages with 30 household triads (90 participants). Pre/post surveys of all participants were analyzed using paired sample nonparametric tests and in-depth interviews with a subset of 45 participants were transcribed and analyzed thematically. Results Sumadhur significantly impacted (p < .05) norms related to pregnancy spacing and timing, and sex preference of children, as well as knowledge about family planning benefits, pregnancy prevention methods, and abortion legality. Family planning intent also increased among newly married women. Qualitative findings revealed improved family dynamics and gender equity, and shed light on remaining challenges. Conclusions Entrenched social norms surrounding fertility and family planning contrasted with participants' personal beliefs, highlighting needed community-level shifts to improve reproductive health in Nepal. Engagement of influential community- and family-members is key to improving norms and reproductive health. Additionally, promising interventions such as Sumadhur should be scaled up and reassessed.